Harm reduction measures in prison (Methadone treatment) and its effects on quality of life promotion - Iraj Esmaili (Drug Control Headquarters, Research and Education Office, 2009)
Preface:Most of the people, who are incarcerated, are considered as competent labor force and in the most of the times they are young people of the society and they would return to the community after serving a period of conviction. Promoting health condition in prison population and effective use of imprisonment period is a safe way to rehabilitate the prisoners. Harm reduction programs begin with supporting "a group of people who have risky behaviors or can not quit drug abuse or do not like give them up". The philosophy of harm reduction is based on pragmatism theory. In fact harm reduction paradigm is focused on the individual risky behaviors reduction. The practical principles of this paradigm are based on empowerment of risky personalities. Harm reduction defines the pattern of substance abuse as a range, from negative consequences for abusers and society to abstinence. Method: The first part of this six months study was cross-sectional and the second phase of it has been conducted as a longitudinal survey in six months period. To study the objectives and to collect the data, a demographic questionnaire andSF-36 questionnaire has been used. Finding:In three different prisons Evin (27 person 10.8%), Rajaeeshahr (88 person 35.2%) and Ghezelhesar (135 person 54.0%) were selected. According to the data the prisoners who received the Methadone treatment during this 6 months, have been improved in Physical Function (p<0.010), Bodily Pain (p<0.003), Mental Health (p<0.019), Vitality (p<0.001), General Health (p<0.017) and Social Function (p<0.041) dimensions quality of life status significantly. There were not seen any improvement in Role Physical (p<0.0710 and Role Emotional (p<0.313) dimensions. Conclusion: In a look, it is obvious that the harm reduction measures which have been taken for prisoners under the coverage of Methadone treatment will be effective in improving their quality of life conditions.